Lécba stavů s pretízením zelezem podáváním perorálního chelátoru L 1 (Deferiprone) - Cermák, J; Brabec, V (Vnitrni lekarstvi, 1994)
Nine iron overloaded patients were treated with L1--Deferiprone (1,2-dimethyl-3-hydroxypyrid-4-one) in daily dose 3 g (40-50 mg/kg) for 12 weeks. In 7 patients the efficiency of L 1 treatment was compared to the therapeutic effect of the same dose of desferrioxamine (Desferal). A significant increase in urinary iron excretion was observed after administration of both chelating agents. Iron excretion after L 1 treatment was approximately 65% of that obtained with Desferal. The amount of excreted iron correlated with the amount of iron stores before chelation. A significant decrease in transferrin saturation, serum and red cell ferritin was observed after treatment with Desferal, L 1 administration caused a significant decrease only in serum ferritin level. However, all the parameters reflecting iron stores remained increased when compared to normal values after 12 weeks of chelation therapy. An incomplete absorption from gut and some reutilization of chelated iron may be responsible for less potent iron chelation by L 1 in comparison to Desferal. A low tolerance of the drug together with repeated nausea and vomiting were the most frequent adverse effects observed in the course of L1 administration. L 1 treatment had to be discontinued due to repeated vomiting in one patient and due to progressive granulocytopenia and thrombocytopenia in another patient. Because of the side effects more clinical studies with L 1 are needed before its introduction in wide clinical practice.
Keywords: deferoxamin; Administration, Oral; chelátory železa; Iron Chelating Agents; pyridony; Deferoxamine; Pyridones; aplikace orální; Deferiprone; Hemosiderosis; Humans; deferipron; lidé; hemosideróza